Earth resources and environmental impacts - O'Hara, Kieran D (Wiley, 2014)
Includes bibliographical references and index; "Earth Resources and Environmental Impacts uses everyday examples and current issues to help readers understand how mineral, water and energy resources - and the impacts of their use and extraction - affect their daily lives. A historical perspective makes the material in this text fascinating by showing readers that the earth's resources have always been fundamental to society, even as far back as the Stone Age. Environmental impacts and sustainable use of energy and mineral resources are emphasized, as well as a section targeted to medical geology. With the increase of public interest surrounding environmental impacts, readers will appreciate the knowledge gained from this text. "-- Provided by publisher.